Perinatal Experiences of Women With Physical Disabilities and Their Recommendations for Clinicians - Smeltzer, Suzanne C. (J Obstet Gynecol Neonatal Nurs, 2016)
OBJECTIVE: To explore the perinatal experiences of women with physical disabilities (WWPD) and their associated recommendations for maternity care clinicians to improve care. DESIGN: A mixed-method study was conducted using a semi-structured interview guide to identify the experiences of WWPD. This qualitative descriptive study is part of a larger study and was conducted to examine the perceptions of WWPD about their interactions with maternity care clinicians and their recommendations for maternity care clinicians to improve care. PARTICIPANTS: Twenty-five women with physical disabilities who gave birth within the last 10 years and were 21–55 years of age were recruited and agreed to participate in the study. METHODS: Participants were asked about their interactions with clinicians during pregnancy and their recommendations for clinicians to improve perinatal care for women with physical disabilities. Transcribed interviews were analyzed using content analysis. Themes that emerged from analysis of the interviews were identified and coded. Kurasaski’s coding was used to establish the reliability of the coding. RESULTS: Three themes emerged from analysis of the interview data: clinicians’ lack of knowledge about pregnancy-related needs of WWPD; clinicians’ failure to consider knowledge, experience, and expertise of women about their own disabilities; and clinicians’ lack of awareness of reproductive concerns of WWPD. Women provided recommendations that warrant attention by clinicians who provide perinatal care for women who live with physical disabilities. CONCLUSION: Participants experienced problematic interactions with clinicians related to pregnancy and identified recommendations for maternity care clinicians to address those problems with the goal of improving perinatal health care for WWPD.